2012
DOI: 10.1007/s13224-012-0281-2
|View full text |Cite
|
Sign up to set email alerts
|

Intrapartum Amnioinfusion in Meconium-Stained Liquor: A Case–Control Study

Abstract: Objective The aim of this study was to investigate perinatal outcome and the rate of cesarean section (CS) following intrapartum amnioinfusion in women with meconium-stained amniotic fluid (MSAF). Method A total of 100 women at term in labor with meconium were randomized to infuse transcervical intrapartum amnioinfusion with saline (50) and routine obstetrical care (50). Perinatal outcome and obstetric outcome were recorded and analyzed in both groups by means of Chi-square test. Result The CS rate due to feta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 3 publications
1
5
0
Order By: Relevance
“…Also, Choudhary et al (17) reported that AI during labor was not associated with any significant neonatal complications, but was associated with improved neonatal outcome as evidenced by statistically improved Apgar score at 1 min in newborns of women of study versus control group (10 vs. 37.2%). Moreover, Bansal et al (19) detected significantly lower frequency of respiratory distress of neonate of women received AI than in control group (4% vs. 12 %). Bhatia et al (20) documented that AI is valuable in patients with MSAF as it provided significant relief from variable decelerations in 68.18% vs. 7.1% in control group, significantly increased the chance for having VD with significant reduction of frequency of development of MAS 6% vs. 20 % in control group.…”
Section: Results:-mentioning
confidence: 95%
See 1 more Smart Citation
“…Also, Choudhary et al (17) reported that AI during labor was not associated with any significant neonatal complications, but was associated with improved neonatal outcome as evidenced by statistically improved Apgar score at 1 min in newborns of women of study versus control group (10 vs. 37.2%). Moreover, Bansal et al (19) detected significantly lower frequency of respiratory distress of neonate of women received AI than in control group (4% vs. 12 %). Bhatia et al (20) documented that AI is valuable in patients with MSAF as it provided significant relief from variable decelerations in 68.18% vs. 7.1% in control group, significantly increased the chance for having VD with significant reduction of frequency of development of MAS 6% vs. 20 % in control group.…”
Section: Results:-mentioning
confidence: 95%
“…Also, Butt & Ahmed (18) reported that transabdominal AI is a useful procedure to reduce complications that result from oligohydramnios as AI increases the latency period, and may result in better perinatal outcome by improving birth weight. Thereafter, Bansal et al (19) found the CS rate due to fetal distress was significantly lower in women of received AI than in controls (20% vs. 40.0 %) and Bhatia et al (20) documented that intrapartum transcervical AI is valuable in patients with MSAF as it significantly increased the chance for having VD with significant reduction of frequency of development of MAS (6% vs. 20%).…”
Section: Results:-mentioning
confidence: 99%
“…Hofmeyr et al (2001) showed that the rates of foetal distress and caesarean section were significantly reduced in amnioinfusion group. [5] Bansal et al [3] found that amnioinfusion in cases of meconium-stained amniotic fluid significantly improved neonatal outcome and reduced caesarean section rate. Bhatia P et al [5] also showed decreased caesarean section rate and decreased incidence of meconium aspiration syndrome.…”
Section: Amnioinfusionmentioning
confidence: 99%
“…This will dilute thick meconium and increases amniotic fluid index. Bansal N et al [3] and Bhatia P et al [4] have shown that amnioinfusion in moderate to thick meconium-stained amniotic fluid improves obstetric and neonatal outcome and decrease in operative delivery.…”
mentioning
confidence: 99%
“…[11][12][13][14][15][16] The present study was designed to test the hypothesis that amnioinfusion can reduce the incidence of caesarean deliveries and perinatal morbidity associated with meconium stained amniotic fluid.…”
Section: Introductionmentioning
confidence: 99%